Evaluating the Alignment of the Textbook Easy Steps to Chinese with BSKAP Standards for Mandarin Language Education in Indonesia - Avenida, Quinta; Adi, Dian Prasetyo; Sugiarti, Tati; Lianisyah, Ulfah Yanuar; Rudiansyah (JOM, 2024)
This study aims to evaluate the suitability of the textbook Easy Steps to Chinese, published in China, for Mandarin language education in Indonesia, focusing on its alignment with the standards established by the Badan Standar, Kurikulum, dan Asesmen Pendidikan (BSKAP) (Agency for Standards, Curriculum, and Educational Assessment) and the Merdeka Curriculum. Using a qualitative content analysis method, the research examines the textbook's material, presentation, design, and graphics to assess its effectiveness and relevance in the Indonesian context. The findings indicate that although the textbook provides a well-structured approach with comprehensive teaching materials, it faces challenges in terms of cultural relevance and illustrations that are less suitable for the Indonesian environment. Teachers play a critical role in addressing these gaps by supplementing the textbook with additional materials and cultural adaptations to align with local pedagogical needs and the competency standards of the Merdeka Curriculum. Theoretically, this study highlights the significance of culturally contextualized teaching resources in language acquisition. With proper modifications, Easy Steps to Chinese can serve as an effective resource for Mandarin instruction in Indonesia, though further adjustments are needed to fully align it with the Indonesian educational framework.